PROGNOSTIC SIGNIFICANCE OF GLYCEMIC STATUS ON ADMISSION IN DIABETIC AND NON-DIABETIC PATIENTS WITH ACUTE CORONARY SYNDROME - Padhiar, Abhishek; Shrimali, Lalit; Thacker, Bhavik (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim is to study the relationship between glycemic status at admission and outcome in diabetic and non-diabetic patients with acute coronary+ syndrome (ACS). Methods: This prospective, observational study was conducted on all patients admitted to general wards and ICCU at GMCH, Udaipur, from February 2021 to July 2022. Detailed history and clinical examination were done. HbA1c, RBS, CBC, TROP I, and CPK-MB were done. Investigations were collected at the time of admission and discharge. Results: Among non-diabetic patients, there were 19 patients who had hyperglycemia on admission and 36 had normal sugar. Among diabetic patients, 31 patients had hyperglycemia and 24 patients had normal sugar. 31 patients with hyperglycemia on admission had high HbA1c. 29 patients had cardiac failure (26.36%), 30 with cardiogenic shock (27.27%), 33 with arrhythmias (30%), and 4 with pulmonary edema (3.63%), making cardiac failure the most common complication in the study population. The mean ejection fraction at admission for the non-diabetics with normal sugar was 44.52, for non-diabetics with hyperglycemia was 43, for diabetics with normal sugar was 41.88 and for diabetics with hyperglycemia was 40.95. Conclusion: We conclude that non-diabetics presenting with hyperglycemia on admission are at more risk of having complications of ACS and had more mortality compared to diabetics having normal sugar on admission.